The choice of the method of surgical treatment of varicose veins of the lower extremities in outpatient clinic - A. N. Shikhmetov; N. N. Lebedev; A. M. Zadikyan; N. V. Ryazanov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to compare the results of treatment of varicose veins of the lower extremities using minimally invasive methods in outpatient clinic. MATERIAL AND METHODS. The complex analysis of the treatment of 220 patients with varicose veins of the lower extremities was carried out. The approach to the choice of the volume of surgery was based on the data of ultrasound examination. The results of radiofrequency ablation and laser coagulation of subcutaneous veins were compared. RESULTS. CVI phenomena after EVLO were eliminated in 146 (95.4 %) patients, after RFA – in 62 (92.5 %). Differences in the frequency of obliteration were higher in the RFA group compared with EVLO (rxy=(0.772±0.02); p<0.01); differences in the ablation frequency were more significant after EVLO (rxy=(0.712±0.04); p<0.01), and differences in recanalization frequency were insignificant (rxy=(0.341±0.08); p<0.01). Thus, it was proven the equal efficacy of these methods in removing the vertical reflux in the surgical treatment FBVNC. In general, the efficiency estimated by recanalization frequency after EVLO and RFA was 92.7 %. CONCLUSION. Endovasal methods were highly effective and safe, could be successfully used for eliminating both vertical and horizontal pathological reflux in surgical treatment of FBVNC in outpatient clinic.